ANALISIS PELAKSANAAN PROGRAM COMMUNITY DEVELOPMENT SEBAGAI BENTUK TANGGUNGJAWAB SOSIAL PT ARARA ABADI DISTRIK SOREK DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Raendy Herlangga; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Corporate Social Responsibility or corporate social responsibility is one of the obligations that must be undertaken by the company in accordance with the contents of article 74 of law number 40 of 2007 concerning limited liability company (UUPT). The Company is guided to exercise and grant community and environmental rights mandated by law in the company. CSR is the logical consequence of the state-funded human rights to the company to survive and develop within an environmental area. As a large company PT Arara Abadi conducts natural exploration in an environment, either directly or indirectly in contact with local ecosystems. It states that PT Arara Abadi must be responsible for all consequences that are deliberate or unintentional to the stakeholders. The purpose of this research is to know and analyze the implementation of community development program as social responsibility form of PT Arara Abadi Sorek district in Improving Community Welfare.The method used in this research is descriptive qualitative method. The subjects were determined based on purposive techniques consisting of the head of the community development team of PT Arara Abadi Sorek District, the chairman of Mitra Abadi, and 3 members of Mitra Abadi institution. Data collection techniques include observation, interviews and documentation. Data analysis techniques use Miles and Huberman's interactive model. While the data validity checking technique includes triangulation and reference adequacy.The results of the study on the implementation of community development programs as a form of social responsibility of PT Arara Abadi in Improving Community Welfare concluded that it was quite good. PT Arara Abadi has done its social responsibility through a partnership program between the company and the community, especially local people. The partnership is realized in the Makmur Peduli Api Village program (DMPA) to assist in the improvement of the welfare of the long-term local community by providing production facilities to the community for 2 years the capital will beReturned to the company to be restored to other communities where the village of Lubuk Keranji Timur where the partnership program was conducted.